Seismic Study of Skew Bridge Supported on Laminated-Rubber Bearings - Xueshan Liu; Wei Guo; Jianzhong Li; Hua Zhang (Advances in Civil Engineering)
Skew bridges consisting of simply supported girders, continuous decks, and laminated-rubber bearings are widely used in western China; however, they are highly vulnerable to strong earthquakes. To investigate the seismic performance of skew bridges considering the sliding behavior of laminated-rubber bearings, the Duxiufeng Bridge located in Sichuan, China, was used as a prototype bridge. This bridge is a skew bridge that suffered seismic damage during the 2008 Wenchuan earthquake. The possible seismic response of this skew bridge under the Wenchuan earthquake was simulated, and the postearthquake repair methods were analyzed considering the effects of bearing types and cable restrainers. Parametric studies, using the finite element method, were also performed to investigate the effects of the skew angle and friction coefficient of the bearings on the seismic response of the skew bridge. The results indicate that pin-free bearings could effectively control the seismic displacement of the bridge, and the cable restrainers with an appropriate stiffness could significantly reduce the longitudinal residual displacements. The effect of skew angles is less significant on skew bridges with laminated-rubber bearings than on rigid-frame skew bridges because of the sliding between the girders and bearings. The residual displacements of the bearings were more sensitive to the variation in the friction coefficient between the laminated-rubber bearings and the girders compared to the maximum seismic displacements.